Effects of the COVID-19 Lockdown on Neuromuscular Performance and Body Composition in Elite Futsal Players. Issue 8 (August 2021) - Spyrou, Konstantinos; Alcaraz, Pedro E.; Marín-Cascales, Elena; Herrero-Carrasco, Rubén; Cohen, Daniel D.; Calleja-Gonzalez, Julio; Pereira, Lucas A.; Loturco, Irineu; Freitas, Tomás T.
Abstract : Abstract: Spyrou, K, Alcaraz, PE, Marín-Cascales, E, Herrero-Carrasco, R, Cohen, DD, Calleja-Gonzalez, J, Pereira, LA, Loturco, I, and Freitas, TT. Effects of the COVID-19 lockdown on neuromuscular performance and body composition in elite futsal players. J Strength Cond Res 35(8): 2309–2315, 2021—Recent world events (i.e., COVID-19 pandemic) led to an unparalleled situation in sports. Players were forced to stay at home for a prolonged period and not allowed to use their team's training facilities or even exercise outdoors. The main aim of this study was to examine the effects of the COVID-19 lockdown on neuromuscular performance and body composition in futsal players. Ten elite male players performed a 10-m sprint, horizontal and vertical jump, and body composition measurements before and after the quarantine (i.e., 70 days). Pre-post confinement differences in horizontal jump distance, countermovement jump variables, sprinting time, and body composition were analyzed by a paired sample t -test and effect sizes (ESs). A large and significant decline was observed in sprint ability ( p = 0.004; ES = 1.31). Small and nonsignificant differences were found in horizontal jump performance ( p = 0.243; ES = −0.39). Nonsignificant differences were observed in countermovement jump (CMJ) height ( p = 0.076; ES = −0.63) but moderate-to-large significant declines were found in CMJ eccentric deceleration impulse, rate of force development, peak power, velocity, and landing peak force ( p ⩽ 0.05; ES = −0.52 – 1.23). Finally, trivial and nonsignificant differences were obtained on body composition parameters. In summary, sprint performance and specific CMJ kinetic variables were significantly affected by long-term reduced training, whereas vertical jump height and horizontal jump distance and body composition were not. Practitioners are advised to implement efficient sprint-oriented and eccentric-oriented training strategies to optimize return to competition after prolonged detraining periods.